Manhwa genre in the book business: history and development prospects - Kuzembay , А.С.; Negizbayeva, М.О.; Kuzembay, У.С. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
Manhwa is a Korean comic book. This term has several meanings. It is used as a definition of animated cartoons and caricatures. Manhwa is similar to the Japanese Manga and the Chinese Manhua. Despite the fact that they have many common features, each of these mini books has its own characteristics. Manhwa was influenced by the history of Korea. The article is devoted to the study of the role of the Manhwa genre in book publishing. In the process of research, an analysis is made between a regular book and an illustration book. An important aspect of the work is the demonstration of the influence of manhwa on the reader’s perception. Attempts have also been made to scientifically substantiate the popularity and success of manhwa comics in South Korea and the usefulness of this genre in domestic book affairs. The purpose of the study is to determine the role of the manhwa genre in publishing. Research methods constitute a review of the scientific literature on the topic, a sociological survey, a comparative analysis. The scientific value of the work lies in the fact that the topic is poorly understood in Kazakhstani science and represents theoretical material for further research, as well as practical significance in publishing.